2015
DOI: 10.1189/jlb.1ru0814-369r
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs function in CD8+T cell biology

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 99 publications
(156 reference statements)
2
36
0
Order By: Relevance
“…The expression of miR‐155 in T cells is induced upon TCR stimulation and nuclear factor (NF)‐κB signalling. By repressing SHIP1, miR‐155 expression induces effector functions such as IFN‐γ secretion . We showed that miR‐155 expression in G‐CSF‐treated and ‐untreated CD8 + T cells was induced after TCR stimulation, which is consistent with the model proposed by Liang et al .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The expression of miR‐155 in T cells is induced upon TCR stimulation and nuclear factor (NF)‐κB signalling. By repressing SHIP1, miR‐155 expression induces effector functions such as IFN‐γ secretion . We showed that miR‐155 expression in G‐CSF‐treated and ‐untreated CD8 + T cells was induced after TCR stimulation, which is consistent with the model proposed by Liang et al .…”
Section: Discussionsupporting
confidence: 89%
“…By repressing SHIP1, miR-155 expression induces effector functions such as IFN-g secretion [14,[41][42][43]. We showed that miR-155 expression in G-CSF-treated and -untreated CD8 1 T cells was induced after TCR stimulation, which is consistent with the model proposed by Liang et al in 2015 [14]. Importantly, the induction of miR-155 expression was lower in G-CSF-treated CD8 1 T cells than in untreated cells.…”
Section: G-csf Affects the Main Elements Of T Cell Activationsupporting
confidence: 90%
“…Their ubiquity makes them potential targets for treatment. Several miRNAs have been shown to alter the activity of APCs, NK cells, T cell differentiation, and effector capacity in mycobacterial infections [32,33]. In a case-control study that enrolled 1098 individuals, single nucleotide polymorphisms located in predicted miR-146a was a unique gene associated with increased risk of leprosy and modulation of TNF levels [34].…”
Section: Mirnamentioning
confidence: 99%
“…On cellular level, 71 of 420 highly characterized miRNAs are differentially expressed upon human T cell activation in vitro[ 8 ]. miRNAs regulate multiple functions in T cells such as TCR signaling, proliferation, differentiation, cytokine secretion and apoptosis[ 9 ] E.g. miR-146a upregulation upon TCR stimulation increases the overall TCR signaling and, thereby, enhances cell activation and cell expansion[ 10 ] miR-155 targets SOCS1, Ship1 and many other mRNAs that participate in type 1 interferon (IFN) signaling and promotes CD8+ T cell proliferation and survival[ 11 , 12 ] miR-17-92 targets the tumor suppressors Pten, ID2, ID3 and the anti-apoptotic bcl-2 and enhances the cell cycle progression of T cells[ 13 ].…”
Section: Introductionmentioning
confidence: 99%